Using the GB2 income distribution - Duangkamon Chotikapanich; William E. Griffiths; Gholamreza Hajargasht; Wasana Karunarathne; D. S. Prasada Rao (Econometrics, 2018)
To use the generalized beta distribution of the second kind (GB2) for the analysis of income and other positively skewed distributions, knowledge of estimation methods and the ability to compute quantities of interest from the estimated parameters are required. We review estimation methodology that has appeared in the literature, and summarize expressions for inequality, poverty, and pro-poor growth that can be used to compute these measures from GB2 parameter estimates. An application to data from China and Indonesia is provided.
Keywords: I32; O15; C13; 330; inequality; poverty; pro-poor growth; GMM estimation